Ion Exchange Kinetics of α-,β-and γ-Picolines: Thermodynamic Parameters - Vardia, Jitendra; Intodia, Kumud; Khaturia, B.C.; Bhat, C.V. (Asian Journal of Chemistry, 2010)
The study of ion exchange and sorption equilibria is of great importance to study the ion exchange resin solute solvent systems. Kinetic study of a system is generally undertaken to know the mechanism of the process, to determine the rate controlling step and to calculate the thermodynamic parameters. This study reports the uptake of α, β and γ-picolines by strongly acidic cation exchange resin, Dowex 50 WX8 (-20, +50) in H+ form from aqueous methanolic media of different composition. The variables studied are the rate of stirring, temperature and solvent medium. The study shows that the systems obey the first order rate laws with respect to α, β and γ-picolines. This paper also reports the thermodynamic parameters: the apparent energy of activation ΔE, the entropy of activation ΔS and the free energy of activation ΔG for different systems studied.